(untitled) (Swiss Medical Weekly, 2022)
BACKGROUND AND AIM: Despite being widely regarded as a major cause of health inequalities, little is known regarding health literacy and its association with certain personal characteristics among older adults in Switzerland. To fill this gap, this study assesses health literacy and its associations with individuals’ social, regional, and health characteristics in a nationally representative sample of adults aged 58 years and older in Switzerland. METHOD: We use data of 1,625 respondents from a paper-and-pencil self-completion questionnaire (cooperation rate: 94.3%) that was administered as part of wave 8 (2019/2020) of the Survey of Health, Ageing and Retirement in Europe (SHARE) in Switzerland. Health literacy is measured using the short version of the European Health Literacy Survey questionnaire (HLS-EU-Q16). The scale includes 16 items whose dichotomised responses allow the construction of different indices and sub-indices aimed at measuring various aspects of health literacy. We use multivariable regressions to explore how respondents’ sociodemographic characteristics are independently associated with health literacy. RESULTS: Overall, 6.8% of the respondents had inadequate health literacy, 24.6% problematic health literacy, and 68.6% sufficient health literacy. There were significant associations between health literacy and individuals’ gender, education, economic situation, and self-rated health. Women had higher levels of health literacy than men (p <0.001). Moreover, a higher education level (p <0.001), fewer financial difficulties (p<0.01), and higher self-rated health (p <0.001) were positively correlated with adequate/higher levels of health literacy. CONCLUSION: One-third of older citizens have difficulties managing health-related issues in Switzerland. Individuals with low education, financial difficulties, and bad self-rated health are particularly at risk of being disadvantaged due to their inadequate health literacy level. These findings call for targeted interventions, such as using simplified health or eHealth information tools, improved patient-provider communication and shared decision-making, promoting lifelong learnings activities and health literacy screening for older patients to increase low health literacy and mitigate its consequences, thereby alleviating remaining social health inequalities in the Swiss population.